Peran Kader Posyandu dalam Pencegahan Stunting: Analisis Partisipasi Masyarakat di Kota Bandar Lampung - Shambono, Adi; Ilmi, Nur; Amrozi, Shoni Rahmatullah (Balai Diklat Keagamaan Bandung, 2025)
Stunting is a nutritional problem that affects infants and toddlers. It occurs due to the nutritional intake a child receives from the womb and into infancy. Stunting in toddlers has a significant impact on children's health, both now and in the future. This study examines the role of Posyandu cadres in stunting prevention efforts in Bandar Lampung, adopting a community participation theoretical lens. A qualitative case study was conducted in ten independent Posyandu units and supported by the analysis of official government data. The findings reveal that cadre participation plays a crucial role in early detection, nutritional counseling, and routine monitoring of child growth. Data from the Bandar Lampung Health Office show a decrease in stunting cases from 520 children in December 2023 to 399 children in May 2024. The cadres’ strong social and personal ties with the community enhance the effectiveness of Posyandu services. This study underscores the importance of strengthening cadre capacity as a key component of community-based stunting prevention strategies. Keywords: stunting; Posyandu; cadre; community participation